Populist politics in Africa - Resnick, Danielle (Oxford University Press, 2019)
Although widely used in reference to the Americas and Europe, the concept of populism has been less frequently applied to political dynamics in sub-Saharan Africa. Populism is variously viewed as a political strategy aimed at fostering direct links between a leader and the masses, an ideational concept that relies on discourses that conjure a corrupt elite and the pure people, and a set of socio-cultural performances characterized by a leader’s charisma, theatrics, and transgression of accepted norms. A cumulative approach that combines all three perspectives allows for identifying episodes of populism in Africa. These include historical cases of populist regimes in the 1980s as well as more contemporary examples of party leaders in the region’s democracies who use populism in their electoral campaigns to mobilize subaltern groups, especially those living in urban areas. As found in other regions of the world, those African leaders who have ascended to the presidency on the back of populism typically exert anti-democratic practices once in office. This reaffirms that populism can allow for greater representation of the poor and marginalized in the electoral process, but that populists’ celebration of popular will and supposedly unmediated ties to the people become convenient justifications for bypassing established institutions and undermining the rule of law.